Continuous range search based on network Voronoi diagram. (19th August 2009) - Xuan, Kefeng; Zhao, Geng; Taniar, David; Srinivasan, Bala; Safar, Maytham; Gavrilova, Marina
Due to the boom of GIS and GPS, various queries in spatial and mobile database become hot spot issues nowadays, typically, range search and k nearest neighbour queries. Both problems have undergone extensive development for many years, from focusing on the Euclidean distance to network distance, and from dealing with static objects to moving objects. In every step forward, there have been many literature reports, but only a few have dealt with Continuous Range Search (CRS) query processing. Even though the existing approach to CRS has an acceptable performance, it is still impractical because the query path needs to be segmented. In this paper, we propose a new approach based on network Voronoi diagram for range search, where the query path does not need to be segmented.